Anthropology at the service of moral science in Nemesio de Emesa - Buganza, Jacob (Logos. Anales del Seminario de Metafísica, 2022)
This work aims to recover the central anthropological theses of De natura hominis of Nemesius of Emesa, a Christian author of the 5th century. The perspective from which this work is approached is moral philosophy, as Telfer has suggested. Following his point of view, the author seeks to highlight how the central characteristics of the human being that Nemesio raises are related to moral virtues.